Motivi urbanistične zasnove Slovenj Gradca - Stanič, Ivan (Urbani izziv, 1999)
The intention of the ammendments and supplemments to the spatial components of planning documents in the muncipality of Slovenj Gradec are, amongst other, novelties to the master plans of particular settlements. The article presents motives and reasons for changing the master plan and the desired contents of spatial document adapted to contemporary social and economic circumstances.
Keywords: master plan; mestni načrti; Slovenj Gradec; town plan; urbanism; urbanistično planiranje; urbanizem